Different Observational Methods and the Detection of Seasonal and Atlantic Influence Upon Phytoplankton Communities in the Western Barents Sea - Orkney, Andrew; Davidson, Keith; Mitchell, Elaine; Henley, Sian F.; Bouman, Heather A. (Frontiers in Marine Science, 2022)
Phytoplankton community composition, and its dependency on environmental variation, are key to understanding marine primary production, processes of trophic transfer and the role of marine phytoplankton in global biogeochemical cycles. Understanding changes in phytoplankton community composition on Arctic shelves is important, because these productive environments are experiencing rapid change. Many different methods have been employed by researchers to quantify phytoplankton community composition. Previous studies have demonstrated that the way in which community composition is quantified can influence the interpretation of environmental dependencies. Researchers must consider both the suitability of the data they collect for monitoring marine ecosystems, as well as the research effort required to collect representative datasets. We therefore seek to understand how the representation of phytoplankton community structure in the western Barents Sea, a rapidly changing Arctic shelf sea, influences the interpretation of environmental dependencies. We compare datasets of cell counts, phytoplankton pigments and bio-optics (absorption spectra), relating them to a suite of environmental conditions with multivariate exploratory analyses. We show that, while cell counts reveal the greatest insight into environmental dependencies, pigment and absorption spectral datasets still provide useful information about seasonal succession and the influence of Atlantic water masses– two key subjects of great research interest in this region. As pigments and optical properties influence remotely-sensed ocean-colour, these findings hold implications for remote detection of phytoplankton community composition.